Altered trafficking of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-type glutamate receptors (AMPARs) in the striatum leads to behavioral changes in emotional responses. (1st January 2015) - Lee, Young; Lee, Hojin; Kim, Hyung-Wook; Yoon, Bong-June
Highlights: Transient expression of G2CT increases surface expression of AMPARs in the striatum. G2CT in the dorsomedial striatum reduces mobility in high-anxiety circumstances. G1CT in the dorsomedial striatum transiently alters anxiety-related behavior. Abstract: The striatum receives and integrates multiple inputs from diverse areas in the brain and plays a critical role in the regulation of motor activity. However, whether the striatum is involved in the alteration of behavior in the presence of emotional challenges is unknown. Here, we examined whether alterations in the surface expression of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-type glutamate receptors (AMPARs) in the dorsal striatum would affect anxiety-related behaviors. We found that the transient expression of G1CT or G2CT, AMPAR-derived peptides, in the dorsomedial striatum led to decreased mobility in high-anxiety circumstances; however, the expression of these peptides in the dorsolateral striatum did not affect anxiety-related behavior. These data suggest that excitatory connections within the dorsomedial striatum play important roles in the control of motor actions in the presence of emotional challenges.